In-vivo blood glucose control by phenolic compound from Vernonia amygdalina, Andrographis paniculata, and Pithecellobium jiringa in Streptozotoxin-induced diabetic rats - Zain, A.M. (American-Eurasian Network for Scientific Information, 2014)
Background: Phenolic compound from three plant species, Vernonia amygdalina, Andrographis paniculata, and Pithecellobium jiringa were extracted with 40, 50 and 60 ethanol in steam water bath shaker. The Gallic acid as phenolic compound representative was determined by HPLC. Among the three selected plants, Pithecellobium jiringa contains the highest amount of Gallic acid. The plant extracts were orally dosed to Streptozotoxin-induced diabetic rats. The ratâs blood glucose was monitored for dose response toward Gallic acid. Significant amount of blood glucose reduction was found after 15 days of treatment of the plant extracts solution containing Gallic acid with the maximum of 31 reduction shown by 25 mg/mL of Pithecellobium jiringa dosed. Plant phenolic compound from Pithecellobium jiringa shows good potential for the treatment of diabetic Type 2. Â© 2014 AENSI Publisher All rights reserved.